Attitude toward physical activity after total hip or knee replacement: A cross-sectional survey study of Dutch and Norwegian patients - Inge van den Akker-Scheek; Martin Stevens; Astrid J. De Vries; Anne Marie Fenstad; Ove Nord Furnes; Håvard Østerås; Bregje E. Raap – van Sleuwen; Katja Saris; Geranda E.C. Slager; Monica Unsgaard-Tøndel; Odd Magne Hals; Ann-Katrin Stensdotter (PLoS ONE, 2026)
Objective To gain insight into the attitude towards physical activity (PA) of Norwegian and Dutch patients after hip or knee replacement, possible differences in attitude between the countries and which factors explain a more positive or negative attitude. Methods A cross-sectional survey study investigating attitude toward PA 6–12 months after hip or knee replacement was conducted in Norway and the Netherlands. Patients received a questionnaire consisting of three parts: demography, received health service, and the survey about attitude toward PA consisting of 32 statements divided into four domains – quality of life, level of PA, function, and kinesiophobia. Attitude was scored on a 4-graded Likert scale. A high score indicated a positive attitude toward PA. Survey responses from the Norwegian and Dutch cohorts were compared using one-way ANOVA for group comparison. To identify factors explaining the outcome of the attitude survey, stepwise regressions were used. Results Data from 732 Norwegian patients and 575 Dutch patients was included in the analyses. Overall, the characteristics of the two cohorts were quite similar, although a significantly greater number in the Norwegian cohort had participated in “prehab”, while the participation in “rehab” was similar. In all four domains the attitude scores were generally high, indicating positive attitudes, with Norwegian patients scoring significantly higher. Higher participation in sports was the strongest explaining factor for a more positive attitude toward PA. Older age was the strongest independent variable explaining a less positive attitude towards PA. Conclusion Patients seem to have an overall positive attitude towards PA after hip or knee replacement. Norwegian patients had a more positive attitude compared to Dutch patients, which could be the result of more formalized and extensive education of the benefits of PA as part of the “prehab” in Norway.